Between Principles and Actions: ASEAN and Indonesia in Dealing With The Political Crisis In Myanmar - Gunawan, Tedi (Global Strategis, 2024)
This article explains the role of ASEAN in addressing the political crisis and human rights violations in Myanmar, focusing on Indonesia's leadership as the ASEAN Chair in 2023. Following the 2021 military coup in Myanmar, which garnered global attention, ASEAN endeavored to formulate the Five Point Consensus through a constructive approach to tackle this crisis, yet its implementation remains constrained. This article uses a case study method to evaluate ASEAN's response to Myanmar's post-coup situation. The initial adoption of the "constructive engagement" approach within the ASEAN context was aimed at resolving this crisis. However, this approach, characterized by non-interference and consensus-building, proved ineffective in driving political change in Myanmar. As the ASEAN Chair, Indonesia assumes a pivotal role in seeking more effective solutions. The study finds that ASEAN demonstrates adaptability in addressing the Myanmar crisis, transitioning from the "constructive engagement" approach to "enhanced interactions." Under Indonesia's leadership, ASEAN deployed a team of the Special Envoy for Myanmar Affairs led by Foreign Minister Retno Marsudi and rebuilt ASEAN's centrality through proactive mediation efforts, diplomatic coordination, engagement with external partners, and commitment to regional stability and peace. Additionally, ASEAN's intervention with restrictions on Myanmar's participation in various regional activities serves as a form of 'pressure' to encourage cooperation and accountability. Through these enhanced interactions, ASEAN and Indonesia played a more active role in mediating the crisis and promoting reconciliation among all stakeholders involved. Keywords: ASEAN; Indonesia; Myanmar Coup; Constructive Engagement; Enhanced Interactions Artikel ini menjelaskan peran ASEAN dalam mengatasi krisis politik dan pelanggaran hak asasi manusia di Myanmar, dengan fokus pada kepemimpinan Indonesia sebagai Ketua ASEAN pada tahun 2023. Pasca kudeta militer tahun 2021 di Myanmar yang menyita perhatian global, ASEAN berupaya merumuskan Lima Poin Konsensus melalui pendekatan konstruktif untuk mengatasi krisis ini, tetapi implementasinya masih terkendala. Dengan menggunakan metode studi kasus, artikel ini mengevaluasi respons ASEAN terhadap situasi pasca kudeta di Myanmar. Penerapan awal menggunakan pendekatan "constructive engagement" dalam konteks ASEAN bertujuan untuk menyelesaikan krisis ini. Namun, pendekatan yang bercirikan non-intervensi dan membangun konsensus, terbukti tidak efektif dalam mendorong perubahan politik di Myanmar. Sebagai Ketua ASEAN, Indonesia mempunyai peran penting dalam mencari solusi yang lebih efektif. Studi ini menemukan bahwa ASEAN menunjukkan kemampuan beradaptasi dalam mengatasi krisis Myanmar, melakukan transisi dari pendekatan "constructive engagement" ke "enhanced interactions." Di bawah kepemimpinan Indonesia, ASEAN mengerahkan tim Utusan Khusus untuk Urusan Myanmar yang dipimpin oleh Menteri Luar Negeri Indonesia dan membangun kembali konsep sentralitas ASEAN melalui upaya mediasi proaktif, koordinasi diplomatik, keterlibatan dengan mitra eksternal, dan komitmen terhadap stabilitas dan perdamaian kawasan. Selain itu, intervensi ASEAN dengan pembatasan partisipasi Myanmar dalam berbagai kegiatan regional merupakan bentuk 'tekanan' untuk mendorong kerja sama dan akuntabilitas. Melalui peningkatan interaksi ini, ASEAN dan Indonesia memainkan peran yang lebih aktif dalam memediasi krisis dan mendorong rekonsiliasi di antara seluruh pemangku kepentingan yang terlibat. Kata-kata Kunci: ASEAN; Indonesia; Kudeta Myanmar; Keterlibatan Konstruktif; Interaksi yang Ditingkatkan